On top of the cloud : how CIOs leverage new technologies to drive change and build value across the enterprise - Muller, Hunter, 1960- (Hoboken, NJ : J. Wiley, 2012)
'On Top of the Cloud provides an actionable framework for developing and executing a profitable cloud strategy. The book focuses on nine specific critical areas where success is imperative: (1) Software as a Service (SaaS); (2) Platform as a Service (PaaS); (3) Infrastructure as a Service (IaaS); (4) People (Recruiting, Hiring, Training, Elevating); (5) Process Evolution; (6) Change Management; (7) Governance; (8) Security; (9) Strategic Sourcing. Each of the objectives is thoroughly explained in simple, straightforward language, accompanied by original graphics, charts and illustrations. All of the chapters are fleshed out with real-world stories and revealing anecdotes gathered from the author's exclusive interviews with dozens of colleagues, thought leaders and IT experts from major competitive organizations in markets all over the world'--
Includes bibliographical references (p. 221-223) and index.
Keywords: Information technology -- Management; Technological innovations -- Management; Cloud computing; Chief information officers